Multi-gene analysis of Symbiodinium dinoflagellates: a perspective on rarity, symbiosis, and evolution - Xavier Pochon; Hollie M. Putnam; Ruth D. Gates (PeerJ, 2014)
Symbiodinium, a large group of dinoflagellates, live in symbiosis with marine protists, invertebrate metazoans, and free-living in the environment. Symbiodinium are functionally variable and play critical energetic roles in symbiosis. Our knowledge of Symbiodinium has been historically constrained by the limited number of molecular markers available to study evolution in the genus. Here we compare six functional genes, representing three cellular compartments, in the nine known Symbiodinium lineages. Despite striking similarities among the single gene phylogenies from distinct organelles, none were evolutionarily identical. A fully concatenated reconstruction, however, yielded a well-resolved topology identical to the current benchmark nr28S gene. Evolutionary rates differed among cellular compartments and clades, a pattern largely driven by higher rates of evolution in the chloroplast genes of Symbiodinium clades D2 and I. The rapid rates of evolution observed amongst these relatively uncommon Symbiodinium lineages in the functionally critical chloroplast may translate into potential innovation for the symbiosis. The multi-gene analysis highlights the potential power of assessing genome-wide evolutionary patterns using recent advances in sequencing technology and emphasizes the importance of integrating ecological data with more comprehensive sampling of free-living and symbiotic Symbiodinium in assessing the evolutionary adaptation of this enigmatic dinoflagellate.